An exergy-based analysis of temperature profiles for an over-pressure reflow oven technology - Esfandyari, Alireza; Landskrone, Torben; Syed Khaja, Aarief Hussain; Franke, Jörg (ASME 2015 International Mechanical Engineering Congress and Exposition, IMECE 2015, 2015)
In electronics assembly, the convection based soldering technologies in the production lines consumes massive resources and energy. The recent advancements in soldering technologies consume comparatively higher resources and needs to be optimized for resource efficient production which is also the motivation for the present work. This study is devoted to quantify the resource consumption and qualify this consumption through exergy flows in an over-pressure reflow technology as an energy intensive process in electronics manufacturing. The analysis implies on a big saving potential for energy consumption specifically during the over-pressure process which also defines the void reduction quality of solder joints. Exergy efficiency is the fraction of the work potential of the heat that is converted to work, and it illustrates the quality of consumed resources during the soldering oven process. Shortening the production lead-time, and increasing the production rate increase the efficiency of exergy and prevents wastage of usable energy. Furthermore, the set-up improvements for the temperature profiles are necessary, and the changes toward developing new technologies in pre-heating and over-pressure chamber zones are mandatory if a high efficiency of resources used is expected.